Profiling the metabolome of adenomyosis-associated infertility patients to predict the pregnancy outcome of frozen embryo transfer - Zhang, Wen; Chen, Yidong; Han, Bing; Li, Rong; Ma, Caihong; Qiao, Jie (Frontiers in Endocrinology, 2025)
ObjectiveThis study explores the metabolic profiles in the peripheral blood of infertile patients with adenomyosis (ADM) to identify key metabolites affecting pregnancy outcomes in these patients undergoing frozen embryo transfer (FET). Our goal is to create a metabolite-based clinical prediction model for pregnancy outcomes in adenomyosis-associated infertility.MethodsThis prospective cohort study from the Reproductive Center at Peking University Third Hospital enrolled 94 infertile patients with adenomyosis and control (CTRL) patients undergoing FET. We divided these patients into four groups based on clinical pregnancy success: ADM-Success, ADM-Fail, CTRL-Success, and CTRL-Fail. We collected peripheral blood on the day of embryo transfer and analyzed metabolites using ultrahigh-performance liquid chromatography-tandem mass spectrometry. We compared metabolome differences among the four groups using bioinformatics and evaluated the diagnostic performance of metabolites for predicting pregnancy outcomes using receiver operating characteristic curves.ResultsWe found the metabolic differences between ADM-Success group and ADM-Fail group, and established a “5 metabolites + age” panel (5 metabolites combined with woman’s age panel), which could effectively predict pregnancy outcomes of adenomyosis patients, and the area under the curve was 0.879 (P<0.001). The 5 metabolites included Androsterone, Propionic acid, Glycocholic acid, 2,6-Dihydroxypurine, Deoxycorticosterone. And this study explored the metabolic differences between adenomyosis group and control group.ConclusionsA “5 metabolites + age” panel could effectively predict pregnancy outcomes of adenomyosis patients who undergoing FET. There were notable differences in plasma metabolic profiles between adenomyosis-associated infertility and control patients.